Optical and other solitons for the fourth-order dispersive nonlinear Schrodinger equation with dual-power law nonlinearity - Al Qurashi, Maysaa Mohamed; Yusuf, Abdullahi; Aliyu, Aliyu Isa; İnç, Mustafa (Academic Press Ltd- Elsevier Science Ltd, 2017)
In this work, the soliton solutions of the fourth-order nonlinear Schrodinger. equation (NLSE) with dual-power law nonlinearity is analyzed using Ricatti-Bernoulli (RB) sub-ODE and modified Tanh-Coth methods. We obtain new solutions that are not in existence in previous time. The constraint conditions between the soliton parameters are determined. The solutions we obtained may be used to explain and understand the physical nature of the wave spreads in the most dispersive optical medium. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: NLSE; Dual power law; Ricatti-Bernouli sub-ODE method and modified Tanh-Coth method